Level of Postnatal Checkup in Ethiopia – Implications for Child Health Services - Birhane, Binyam Minuye; Bayih, Wubet Alebachew; Mekonen, Demewoz Kefale; Chanie, Ermias Sisay; Demis, Solomon; Shimelis, Habtamu; Asferie, Worku Necho; Abebe, Eskeziaw; Addisu, Dagne; Nibret, Gedefaye; Endalamaw, Aklilu; Munye, Tigabu; et al. (Frontiers in Pediatrics, 2022)
Background: High neonatal mortality rates continue to be a major public health issue in Ethiopia. Despite different maternal and neonatal care interventions, neonatal mortality in Ethiopia is at a steady state. This could be due to the low utilization of neonatal checkups. Thus, assessing the level and predictors of postnatal checkups nationally could provide important information for further improving neonatal health care services. Thus, assessing the level of neonatal checkups and its predictors at the national level could provide an input on improving neonatal health care service. Methods: A secondary data analysis of the 2016 Ethiopia Demographic and Health Survey (EDHS) was performed on 7586 women who had live births in the two years prior to the survey. All variables with a p-value ≤ 0.25 in the bivariable analysis were entered into the final model for multivariable analysisAll variables with a P-value < 0.25 during bi-variable were considered for multivariable binary logistic regression analysis, and the level of statistical significance was declared at a P-value ≤ 0.05. Results: According to the national survey, only 8.3 percent [95 % CI: 8.19, 8.41] of neonates received postnatal checkups. AboutMore than two-thirds of women, 62.8 % had antenatal care visits, 67.9 %, gave birth at home, 62.8 % had antenatal care visits, aand 95.7 % were unaware of neonatal danger signs. Distance from health care institutions [AOR] = 1.42; 95 % CI: 1.06, 1.89], giving birth in a health carehealthcare facility [AOR = 1.55; 95 % CI: 1.12, 2.15], antenatal care visit [AOR = 3.0; 95 % CI: 1.99, 4.53], and neonatal danger signs awareness [AOR = 3.06; 95% CI: 2.09, 4.5] were all associated with postnatal care visit. Conclusions: The number of neonates who had a postnatal checkup was low. As a result, increasing antenatal care visit utilization, improving institutional delivery, raising awareness about neonatal danger signs, increasing access to health care facilities, and implementing home-based neonatal care visits by health care healthcare providers could all help to improve postnatal checkups.